Development of Teaching and Learning Materials for Geometry through Problem-based Learning Model - Chen, Wen Haw (Sains Humanika, 2013)
Problem-based learning (PBL) model can help students to study oneself from the question even more. This research hopes to think Luce Chapel in Tunghai University as the model to incorporate geometry in mathematics. The method comes to develop the teaching aid of the model of Luce chapel to excite students of different stages thinking deeply the designed questions and to assist teaching. We include the mathematics concepts incorporated in the teaching aid: The structure of 3 – dimensional space for elementary school students comes by way of designing and counting the building blocks; Lead the junior high school students to calculate the surface area , volume, and pile up the building blocks to utilize arithmetic progression; Let the high school student utilize elementary functions and conic sections. Moreover, by the fact that the chapel tiles levelly and smoothly, some advanced geometric concepts can be also introduced to university students.